2011
DOI: 10.1186/cc10220
|View full text |Cite
|
Sign up to set email alerts
|

Deceased donor neutrophil gelatinase-associated lipocalin and delayed graft function after kidney transplantation: a prospective study

Abstract: IntroductionExpanding the criteria for deceased organ donors increases the risk of delayed graft function (DGF) and complicates kidney transplant outcome. We studied whether donor neutrophil gelatinase-associated lipocalin (NGAL), a novel biomarker for acute kidney injury, could predict DGF after transplantation.MethodsWe included 99 consecutive, deceased donors and their 176 kidney recipients. For NGAL detection, donor serum and urine samples were collected before the donor operation. The samples were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 44 publications
(46 reference statements)
1
48
2
1
Order By: Relevance
“…In a cohort of 99 deceased donors and 176 kidney transplant recipients, Hollmen et al found NGAL measured in deceased-donor urine samples did not predict DGF as defined by any dialysis in the first week of transplant, but higher donor urine NGAL concentrations were associated with a longer duration of post-transplant dialysis and lower 1-year allograft survival. 28 A potential explanation for the contrasting findings is that our cohort had substantially greater power to detect the association with DGF. We also did not have detailed data on duration of post-transplant dialysis in the entire cohort, precluding our ability to examine DGF severity.…”
Section: Discussionmentioning
confidence: 58%
“…In a cohort of 99 deceased donors and 176 kidney transplant recipients, Hollmen et al found NGAL measured in deceased-donor urine samples did not predict DGF as defined by any dialysis in the first week of transplant, but higher donor urine NGAL concentrations were associated with a longer duration of post-transplant dialysis and lower 1-year allograft survival. 28 A potential explanation for the contrasting findings is that our cohort had substantially greater power to detect the association with DGF. We also did not have detailed data on duration of post-transplant dialysis in the entire cohort, precluding our ability to examine DGF severity.…”
Section: Discussionmentioning
confidence: 58%
“…12 Additionally an association with delayed graft function following renal transplantation is now emerging. 13,14 Critical evaluations of the literature highlighting the potential of NGAL and other markers now recommend larger, clearly designed prospective studies and with attention to issues such as thorough statistical analysis, assays used and confounding factors such as chronic kidney disease. 8,11 Currently (as at 1 September 2012) on the www.clinicaltrials.gov website alone there are 73 studies involving measurement of NGAL.…”
Section: Introductionmentioning
confidence: 99%
“…However, failed to predict DGF in the receiver operating characteristic (ROC) analysis. Reese et al (35) also documented the association of donor uNGAL with consequent DGF, but with lower incidence in comparison to the findings of Hollmen et al (34). Furthermore, both uNGAL and uL-FABP were in association with a lower estimated GFR (eGFR) at sixmonths, but only in recipients in absence of DGF.…”
Section: Urine Biomarkersmentioning
confidence: 84%
“…In contrast, considering the current restrictions to allograft quality appraisal, donor urinary biomarker analysis could serve as a valuable assessment tool to decide on allograft selection and in addition make decisions on early perioperative recipient management. Hollmen et al (34) examined the predictive value of uNGAL levels in deceased donors for the first time. None of the donors had clinically established AKI previous to death.…”
Section: Urine Biomarkersmentioning
confidence: 99%